Employing circular economy on offshore D&A via life cycle assessment - Anuar, Hazleen (2020)
Oil and gas will continue to play a very important role coupled with renewable energy sources in an energy mix scenario. The decommissioning of aging offshore oil and gas platforms will increase dramatically in the next coming years. In order to help a decision making process, a project named RELife (Renewable Energy for a new Life of offshore platforms) has been developed with the main goal of to develop a model for the reuse of offshore Oil & Gas platforms at end-of-life stage for the production of renewable energy. Through consideration of two types of platforms (4-legged platform with 3 or 4 production wells), various technical scenarios are studied and investigated and for each scenario also the environmental and economic feasibility is evaluated. In addition, all the sub-models are compared with a standard decommissioning process. The evaluations are made for both the Adriatic Sea and the North Sea, two geographic areas with different availabilities of renewable resources.